Marketing strategies for rubber seed oil and cake - Ogowewo N
The paper stresses the difficulty in designing marketing strategies for rubber seed oil and cake in Nigeria in view of the fact that production is not yet commercialised. However it identifies merchandising, physical distribution and facilitation functions as elements of the potential marketing strategies that might be adopted and suggests as suppliers are linked to the end users of rubber seed oil and cake (oil paint industry and livestock feed millers respectively) either directly or through the rubber seed oil millers and Nigerian Rubber Board. The latter has a monopoly of export marketing of rubber seed oil and cake. The paper points to inadequacy of seed supplies, poor storage and ineffective pricing as the likely marketing problems and advocates strengthening of the relevant research and development institutions to ensure effective marketing of the rubber seed oil and cake following commercialisation of production.
Keywords: Marketing; Rubber seed cake; Rubber seed oil